Bushfire‐Induced Water Balance Changes Detected by a Modified Paired Catchment Method. Issue 11 (28th October 2022) - Xu, Zhenwu; Zhang, Yongqiang; Zhang, Xuanze; Ma, Ning; Tian, Jing; Kong, Dongdong; Post, David
Abstract: While bushfires are often regarded as a vital trigger that alters the partitioning of hydrological fluxes, their role in water balance changes remains poorly quantified, especially in regions where the impacts of frequent bushfires and climate variability overlap. Here, we estimated the fire‐induced water balance changes based on a modified paired catchment method that considers the partial effect of annual precipitation differences. In the application for eight forested catchments impacted by the 2009 Victorian Bushfires with multiple burned areas (12%–89%), we found that evapotranspiration declined by 33 ± 20 mm yr −1 (mean ± standard deviation) and streamflow increased by 68 ± 32 mm yr −1 during the post‐fire decade. For the interannual changes within this decade, the decline in evapotranspiration due to fires gradually recovered after the first year since bushfires, while the increase in streamflow mostly peaked in the second or third year and diminished in subsequent years. We surmised that such asynchronous responses of the two fluxes to bushfires occurred with the initial increase and the later decrease in terrestrial water storage. Averaged for the post‐fire decade, there seems to be an overall decline in terrestrial water storage for burned catchments relative to unburned catchments. Plain Language Summary: Apart from high temperature and burning biomass, bushfires can induce dramatic changes in plant water use and water yield in catchments during post‐fire years. Its impact on water resources is often compounded with climate change. In early 2009, large forest fires swept many parts of Victoria, Australia. Using a set of burned and unburned catchments and high‐resolution water balance data, we found that bushfires caused asynchronous decreases in evapotranspiration and increases in streamflow. The different magnitudes of the changes in the two fluxes may indicate a decline in terrestrial water storage for burned catchments when compared with that of unburned catchments. These findings advance our understanding of the role of bushfires on hydrological fluxes and terrestrial water storage in a changing climate. Key Points: Paired catchment method is modified for the use of detecting changes in catchment water balance, including water storage change The decreased evapotranspiration and the increased streamflow due to the 2009 Victorian Bushfires are temporally asynchronous The water storage increase in a wetter climate may be less than expected for burned catchments